Effects of diamine isomers on the properties of colorless and transparent copoly(amide imide)s. Issue 48 (13th September 2021) - Choi, Moon Young; Lee, Seon Ju; Kwac, Lee Ku; Kim, Hong Gun; Chang, Jin-Hae
Abstract : The thermal- and mechanical-properties and optical transparency of the copoly(amide imide) films with different BPA monomer contents were investigated. Abstract : To fully understand the structure–property relationship of aromatic copoly(amide-imide)s (Co-PAIs) and determine which factors lead to chain rigidity, we prepared two series of Co-PAIs. They were synthesized from two types of amine monomers containing m - and p -isomers and different ratios of 4, 4′-(hexafluoroiso-propylidene)diphthalic anhydride (6FDA) and 4, 4′-biphthalic anhydride (BPA). m -Substituted and p -substituted N, N ′-[2, 2′-bis(trifluoromethyl)-4, 4′-biphenylene]bis(aminobenzamide) (MPAB) diamine isomers were synthesized from 3- and 4-nitrobenzoyl chloride and 2, 2′-bis(trifluoromethyl) benzidine (TFB), respectively. The Co-PAI films were synthesized from poly(amic acid) (PAA), via solution-casting, followed by thermal imidizations. The thermal- and mechanical-properties and optical transparency of the Co-PAI films with different BPA monomer contents were investigated. We also investigated the effects of the different MPAB isomers on the Co-PAI structures. Compared with the m -substituted MPAB Co-PAI films, the p -substituted MPAB Co-PAI films have superior thermo-mechanical properties at the same monomer content. However, the optical transparencies of the m -MPAB Co-PAIs are slightly better than those of the p -MPAB Co-PAIs.